+0  
 
0
51
4
avatar

The roots of y^2 + 5y - 11 = 0 are a and b. Find (a + 3)(b + 3).

 May 3, 2020

Best Answer 

 #1
avatar
+1

By Vieta's formulas, a + b = 5 and ab = -11, so (a + 3)(b + 3) = ab + 3(a + b) + 9 = -11 + 3*5 + 9 = 13.

 May 3, 2020
 #1
avatar
+1
Best Answer

By Vieta's formulas, a + b = 5 and ab = -11, so (a + 3)(b + 3) = ab + 3(a + b) + 9 = -11 + 3*5 + 9 = 13.

Guest May 3, 2020
 #3
avatar+30046 
+2

Almost right guest, but a+ b = -5 not +5

 

Using that your final formula becomes  -11 - 3*5 + 9 = -17

Alan  May 4, 2020
 #2
avatar+87 
0

It said it wasn't correct. Thank you for trying though!

 May 4, 2020
 #4
avatar+87 
0

Great! Thanks!

 May 4, 2020

24 Online Users

avatar